Microteaching: A Life Based Learning Approach in a Prospective Teachers Perspective - Sulastri Sulastri; Dhika Maha Putri; Moh. Danang Bahtiar (AIBPM Publisher, 2019)
The education curriculum in Indonesia requires students to be able to find concepts and link them with the problems in the real world. This makes a teacher, must be able to facilitate students in building their own understanding. Microteaching, is a subject about the basic teaching that is taken by every student majoring in education as a Prospective Teacher. Based on this, the substance of the microteaching course must be able to prepare teachers in accordance with the applicable curriculum requirements. On the other hand, the life-based learning approach that promotes learning originating from life is considered very suitable to represent the demands of the curriculum. This study aims to interpret student perspectives on microteaching learning through a life based learning approach. Based on the results of the study, it is known that students find it easier to understand microteaching courses that uses a life based learning approach.